2022
DOI: 10.2340/17453674.2021.806
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperatively local infiltration anesthesia in hemiarthroplasty patients reduces the needs of opioids: a randomized, double-blind, placebo-controlled trial with 96 patients in a fast-track hip fracture setting

Abstract: Background and purpose — Local infiltration analgesia (LIA) is commonly used as a component in multimodal analgesia. Pain management directed towards hip fracture patients operated on with hemiarthroplasty is often based on knowledge regarding pain treatment following elective surgery. In this elderly patient population, it is of value to clarify whether adding local infiltration analgesia (LIA) to the postoperative analgesic regimen might reduce postoperative pain or have an opioid-reducing effect. Patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…In order to confirm Kerr and Kohan's findings, several studies have been executed. Conflicting evidence has been reported [2][3][4][5][6]8,9,11,12,[14][15][16][17][18][19] . However, consulting and summarizing the literature to date, The Enhanced Recovery consumption of piritramide or tramadol, but an analysis of binary results whether the patients had taken opioids at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to confirm Kerr and Kohan's findings, several studies have been executed. Conflicting evidence has been reported [2][3][4][5][6]8,9,11,12,[14][15][16][17][18][19] . However, consulting and summarizing the literature to date, The Enhanced Recovery consumption of piritramide or tramadol, but an analysis of binary results whether the patients had taken opioids at all.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been conducted reporting contradictory results regarding the efficacy of LIA in hip arthroplasty [2][3][4][5][6]8,11,12,14,15,19,21,22 . However, as only recent studies have implemented an anterior approach, more research is advocated.…”
Section: Introductionmentioning
confidence: 99%
“…3 динамика интенсивности боли обеспечена действием именно тафалгина. Такой принцип анализа анальгетической эффективности все чаще встречается в профессиональной литературе [12]. Обращает на себя внимание достаточно быстрый обезболивающий эффект, при котором начало действия отмечается уже через 15 мин после введения препарата, а медиана максимальной анальгетической активности составляет 40 мин.…”
Section: Discussionunclassified
“…Basmajian et al demonstrated a postoperative pain improvement after the administration of liposomal bupivacaine, and similarly, more recent studies have demonstrated the same. 32–34 Other cocktails like those used in arthroplasty may also be of benefit. 31,35,36 A paucity of evidence exists within the literature exploring these options, representing an area for further study as these cocktails may be used in lieu of or as part of the continuum of pain control.…”
Section: Discussionmentioning
confidence: 99%